Comparison of Hydrothermally-Grown vs Electrodeposited Cobalt Sulfide Nanostructures as Modified Electrodes for Oxygen Evolution and Electrochemical Sensing Applications - Li, Xinyu; Sharma, Surbhi; Arrigan, Damien; Silvester-Dean, Debbie (ELECTROCHEMICAL SOC INC, 2022)
A wide range of electrocatalysts have been developed and implemented for electrochemical applications over the last decades, with researchers typically using either a conventional synthesis method (followed by drop-casting or spray-coating onto the electrode), or directly electrodepositing the catalyst. However, a clear comparison of the different materials synthesis techniques, and how this affects the electrochemical applications, has been less explored. Herein, we report a direct comparison of fabricated cobalt sulfide (CoS) nanostructure-based electrodes prepared by two different methods for two applications: (a) electrochemical water splitting and (b) glucose sensing. CoS is grown in the form of nanoflowers and nanosheets via facile one-pot hydrothermal (HT) and electrodeposition (ED) methods, respectively. Characterization is performed using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), and X-ray photoelectron spectroscopy (XPS). It is observed that the as-fabricated CoS-ED electrode demonstrated enhanced oxygen evolution reaction (OER) performance, a lower overpotential (∼166 mV at 10 mA cm−2), lower charge transfer resistance (∼372 Ω), a lower Tafel slope (86 mV dec−1), and better stability compared to the CoS-HT electrode. Moreover, the CoS-ED electrode-based sensor also exhibited better performance, higher sensitivity, better selectivity, and good stability for electrochemical glucose detection compared to the CoS-HT sensor.